Reverse electrodialysis heat engine with multi-effect distillation: Exergy analysis and perspectives. (15th August 2019) - Ortega-Delgado, B.; Giacalone, F.; Catrini, P.; Cipollina, A.; Piacentino, A.; Tamburini, A.; Micale, G.
Highlights: An exergy analysis of a reverse electrodialysis heat engine is presented for the first time. Irreversibility sources of the system are identified and quantified. The effect of the main operating variables on the exergy efficiency is assessed. High-performing membranes in reverse electrodialysis dramatically improve the overall performance. A maximum exergy efficiency of 24% has been reached. Abstract: The increasing worldwide energy demand is rising the interest on alternative power production technologies based on renewable and emission-free energy sources. In this regard, the closed-loop reverse electrodialysis heat engine is a promising technology with the potential to convert low-grade heat into electric power. The reverse electrodialysis technology has been under investigation in the last years to explore the real potentials for energy generation from natural and artificial solutions, and recent works have been addressing also the potential of its coupling with regeneration strategies, looking at medium and large energy supply purposes. In this work, for the first time, a comprehensive exergy analysis at component level is applied to a reverse electrodialysis heat engine with multi-effect distillation in order to determine the real capability of the waste heat to power conversion, identifying and quantifying the sources of exergy destruction. In particular, sensitivity analyses have been performed to assess the influence of the main operating conditions (i.e. solutions concentration and velocity) and design features (aspect ratio of the pile), characterizing the most advantageous scenarios and including the effect of new generations of membranes. Results show that the multi-effect distillation unit is the main source of exergy destruction. Also, using high-performing membranes, inlet solutions concentration and velocity of 4.5–0.01 mol/L and 0.2–0.36 cm/s, respectively, a global exergy efficiency of 24% is reached for the system, proving the high potential of this technology to sustainably convert waste heat into power.